Epidemiology of Colpocephaly in the Texas Birth Defects Registry, 1999 to 2020 - Yantz, Caitlyn; Shumate, Charles; Betancourt, Dayana; Allred, Rachel; Nguyen, Joanne; Agopian, A.J.; Salemi, Jason; Ahmad, Kaashif (American Journal of Perinatology, 2025)
Colpocephaly is a congenital brain defect characterized by enlargement of the occipital horns of the lateral ventricles. Few population-based studies have focused on this central nervous system (CNS) defect. This study aimed to evaluate the birth prevalence and survival of Texas infants with colpocephaly delivered between 1999 and 2020.Cases from the Texas Birth Defects Registry (TBDR) with a diagnosis of colpocephaly were identified. Unadjusted birth prevalence, 1-year survival estimates, and crude hazard ratios with 95% confidence intervals (CIs) were calculated from data collected from the medical record abstraction and linked vital records. Select maternal and infant variables were assessed overall and across four medical classification groups (presence of isolated, chromosomal, syndromic, or multiple major defects).From 1999 to 2020, 1,146 cases with colpocephaly were identified. The overall birth prevalence of colpocephaly was 1.36/10,000 live births (95% CI: 1.28–1.44). Significantly higher prevalence was noted for male infants, infants with low birth weight (<2,500 g), and very preterm (<32 weeks) infants. Overall, 1-year survival was 89.5%, with statistically significant differences observed in each medical classification group (e.g., isolated) across levels of maternal education, Texas/Mexico border maternal residence at delivery, infant birth weight, and gestational age.These findings have important implications for pediatric neurology and future research, such as counseling on the prevalence and prognosis of colpocephaly. Additionally, these findings highlight that the population burden of CNS defects may be higher than previously believed, supporting the expansion of research of rare brain defects.
Keywords: colpocephaly; brain reduction defects; CNS defect; congenital brain anomaly